Curcumin and Photobiomodulation in Chronic Viral Hepatitis and Hepatocellular Carcinoma - Ailioaie, Laura Marinela; Litscher, Gerhard (International journal of molecular sciences, 2020)
Immune modulation is a very modern medical field for targeting viral infections. In the race to develop the best immune modulator against viruses, curcumin, as a natural product, is inexpensive, without side effects, and can stimulate very well certain areas of the human immune system. As a bright yellow component of turmeric spice, curcumin has been the subject of thousands of scientific and clinical studies in recent decades to prove its powerful antioxidant properties and anticancer effects. Curcumin has been shown to influence inter- and intracellular signaling pathways, with direct effects on gene expression of the antioxidant proteins and those that regulate the immunity. Experimental studies have shown that curcumin modulates several enzyme systems, reduces nitrosative stress, increases the antioxidant capacity, and decreases the lipid peroxidation, protecting against fatty liver pathogenesis and fibrotic changes. Hepatitis B virus (HBV) affects millions of people worldwide, having sometimes a dramatic evolution to chronic aggressive infection, cirrhosis, and hepatocellular carcinoma. All up-to-date treatments are limited, there is still a gap in the scientific knowledge, and a sterilization cure may not yet be possible with the removal of both covalently closed circular DNA (cccDNA) and the embedded HBV DNA. With a maximum light absorption at 420 nm, the cytotoxicity of curcumin as photosensitizer could be expanded by the intravenous blue laser blood irradiation (IVBLBI) or photobiomodulation in patients with chronic hepatitis B infection, Hepatitis B e-antigen (HBeAg)-positive, noncirrhotic, but nonresponsive to classical therapy. Photobiomodulation increases DNA repair by the biosynthesis of complex molecules with antioxidant properties, the outset of repairing enzyme systems and new phospholipids for regenerating the cell membranes. UltraBioavailable Curcumin and blue laser photobiomodulation could suppress the virus and control better the disease by reducing inflammation/fibrosis and stopping the progression of chronic hepatitis, reversing fibrosis, and diminishing the progression of cirrhosis, and decreasing the incidence of hepatocellular carcinoma. Photodynamic therapy with blue light and curcumin opens new avenues for the effective prevention and cure of chronic liver infections and hepatocellular carcinoma. Blue laser light and UltraBioavailable Curcumin could be a new valuable alternative for medical applications in chronic B viral hepatitis and hepatocarcinoma, saving millions of lives.